Outgroup emotion processing in the vACC is modulated by childhood trauma and CACNA1C risk variant - Krautheim, Johannes; Rietschel, Marcella; Witt, Stephanie (Social cognitive and affective neuroscience, 2018)
Abstract. A high frequency of outgroup contact—as experienced by urban dwellers and migrants—possibly increases schizophrenia risk. This risk might be further
Gesehen am 25.06.2020